A Breakthrough in the Study of the Merya Problem. Review of the book: Matveyev, A. K. (2015). Substratnaia toponimiia Russkogo Severa [Substrate Toponymy of the Russian North] (Vol. 4: Toponimiia merianskogo tipa [Merya-like Toponymy]). Ekaterinburg: Ural University Press - Vladimir V. Napolskikh (Вопросы Ономастики, 2016)
The fourth volume of the study Substrate toponymy of the Russian North written by the outstanding Russian linguist Aleksandr Matveyev and posthumously published by Oleg Smirnov is an important contribution to solving one of the most complicated problems of the East European prehistory which consists in the linguistic and geographical attribution of the Merya people and in understanding their role in the ethnic history of Russia. In order to achieve these goals, Aleksandr Matveyev systematically analysed the most reliable source which is the toponymy of the Merya people’s historical settlement areas. This led him to trace the boarders of the former habitat of the Merya people, to precise the place of the Merya language within the Finno-Volgaic group and to demonstrate the existence of at least two big dialectal sub-areas on the Merya people’s lands. In this review, the author discusses the results obtained by Aleksandr Matveyev, considers some specific problems of his reconstruction of the Merya people’s language and prehistory and formulates some new questions for further investigations.